أثر برنامج إرشادي في تنمية المناعة النفسية لدى طلبة الجامعة - حمد، نادرة جميل (الجمعية العراقية للعلوم التربوية والنفسية, 2021)
إن ضعف المناعة النفسية لدى طلبة الجامعة تشكل خطورة على صحتهم النفسية والجسمية لذلك هدف البحث الحالي إلى تعرف مستوى المناعة النفسية لدى طلبة الجامعة وبناء برنامج إرشادي وفق أسلوب التنظيم لـ جوليان وروتر من أجل تنمية المناعة النفسية للطلبة وقد اعتمدت الباحثة على مقياس دواح ٢٠١٨ لقياس المناعة النفسية لهم بعد إن استخرجت له الخصائص السيكومترية للمقياس وبعدها تم بناء برنامج إرشادي بأسلوب التنظيم والذي تكون من ١٠ جلسات إرشادية بدأت يوم ١٢/ ١/ ٢٠٢٠ وانتهت يوم ١٣/ ٢/ ٢٠٢٠ وأهم النتائج التي توصلت لها الباحثة هي: ١. أن طلبة الجامعة لديهم ضعف في مستوى المناعة النفسية. ٢. أثر البرنامج الإرشادي في رفع مستوى المناعة النفسية لدى الطلبة وتوصلت الباحثة إلى جملة من التوصيات والمقترحات.
The psychological immological weakness of the senior configures dangerous on their ableism and psychological health that why the aim of the present research is to know the level of psychimmunlogical of the senior and building or (construct) heuristic programme according to the organization of (Julian and Roter) to develop the psych immunological of senior. The research has depend on Duah scale 2018 to mesur the psychimmunological for them after getting out the sychometric featurs of the scale than organized heuristic programme his been built (structured). Which consisted of heuristic (10) sessions began on 12 the jan-20 and ended on 13 th feb. 20 and the important results that the researcher has arrived are: 1. the seior have weaknss in the psychimmunological level. 2.the effect of heuristic programme in psychimmunological to in crease the psych immunological level for the senior and the researcher arrived to these recommendations and suggestions.
Keywords: طلبة الجامعة -- المناعة النفسية -- الصحة النفسية -- أسلوب التنظيم -- البرامج الإرشادية -- جامعة بغداد